Application of Ahklakul Karimah to Grade 3 Students at Uptd Sdn 013828 Manis in Islamic Religious Subjects - Br Nasution, Yussi Novia Ningsih; Aziz, Mursal; Hairullah, Hairullah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study discusses the process of learning Islamic religious education at UPTD SDN 013828 Manis, its implementation, and the obstacles faced by teachers in instilling moral values to students at the school. The main objective of this study is to explain how Islamic religious education learning is implemented at UPTD SDN 013828 Manis. This study uses a descriptive qualitative method with a focus on the implementation of Islamic religious education at the school. The author only wants to collect data related to efforts to instill morals in students at UPTD SDN 013828 Manis. Data collection was carried out through observation, interviews, and documentation. The results of the study showed that students have good skills, knowledge, and morals. The process of learning Islamic Religious Education is carried out through various methods, such as meetings, discussions, games, and exemplary stories. The results of the implementation of Islamic religious education at UPTD SDN 013828 Manis are part of an effort to improve students' morals, which can be seen in their daily lives at school, such as: (1) trustworthiness, (2) good behavior, (3) responsibility, (4) discipline, (5) loyalty, and piety, both in learning activities and in carrying out worship. Factors that hinder the instillation of morals in students at this school include internal factors, namely the students themselves and school facilities, as well as external factors, such as the relationship between parents and students, the social environment of the community, and the influence of peers.